Strategi Tim Kreatif dalam Memproduksi Konten YouTube Froyonion “Tapi Boleh Dicoba” - Akhmad Nurfaizi; Happy Prasetyawati (UNISBA Press, 2023)
Abstract. Froyonion’s Youtube channel is “Content But You Can Try”. This content is about an experiment in which Froyonion invites men and women from different work backgrounds to try things for the first time. Creative team strategy in producing. This research uses an approach known as a qualitative approach. Creswell defines present qualitative research as words capable of describing complexity and examining the words in it, providing detailed views of respondents, and conducting surveys with the situation as it is. Strategy is the initial stage for an organization or agency in which there are various steps or stages that are useful for achieving the goals that have been set. Froyonion's video content is produced by a creative team of six people. Next, the creative strategy used by the Froyonion creative team in producing the episode